DEVELOPMENT OF STUDENT WORKSHEET BASED SCIENCE PROCESS SKILLS ON FACTORS AFFECTING REACTION RATE TOPIC - anggi saputra; Noor Fadiawati; nina kadaritna (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
The research aim to develop student worksheet based science process skills on factors affecting reaction rate topic. This research use research and development (R D) method according to Sugiyono (2008).  But in this research, the steps are only done until main product revision. This research have three steps. The 1st step is needs analysis that consist of literature study and field study. The 2nd step is planning and development that consist of planning preliminary product, develop preliminary product, validation, and preliminary product revision. The 3thstep is preliminary field test and main product revision. The results of this research are student worksheet based science process skills on factors affecting reaction rate topic have very good quality for contents suitability aspect with score 98,46%; for readability aspect according to teacher is 98,00% 87,88% according to students; for beauty aspect according to teacher is 98,46% 86,52% according to students.Key words :  student worksheet, science process skills, factors affecting reaction rate topic.